A bio-based 'green' process for catalytic adipic acid production from lignocellulosic biomass using cellulose and hemicellulose derived γ-valerolactone. (1st December 2016) - Han, Jeehoon
Highlights: A bio-based 'green' process for catalytic conversion of corn stover to adipic acid (ADA) is studied. New separations for effective recovery of biomass derivatives are developed. Separations are integrated with cellulose/hemicellulose-to-ADA conversions. Proposed process can compete economically with the current petro-based process. Abstract: A bio-based 'green' process is presented for the catalytic conversion of corn stover to adipic acid (ADA) based on experimental studies. ADA is used for biobased nylon 6.6 manufacturing from lignocellulosics as carbon and energy source. In this process, the cellulose and hemicellulose fractions are catalytically converted to γ-valerolactone (GVL), using cellulose and hemicellulose-derived GVL as a solvent, and subsequently upgrading to ADA. Experimental studies showed maximal carbon yields (biomass-to-GVL: 41% and GVL-to-ADA: 46%) at low concentrations (below 16 wt% solids) using large volumes of GVL solvents while requiring efficient interstage separations and product recovery. This work presents an integrated process, including catalytic conversion and separation subsystems for GVL and ADA production and recovery, and designs a heat exchanger network to satisfy the total energy requirements of the integrated process via combustion of biomass residues (lignin and humins). Finally, an economic analysis shows that 2000 metric tonnes (Mt) per day of corn stover feedstock processing results in a minimum selling price of 633 per Mt if using the best possible parameters.